Resistência em mandioca, Manihot esculenta crantz, à podridão-seca das manivas (Diplodia manihoti SACC.) - Castro, Francisco Edilson de (1978)
"Resistance in cassava, Manihot esculenta Crantz, to Diplodia manihoti Sacc.". Since 1977, the stem dry-rot caused by Diplodia manihoti Sacc., has been found to be one of the most important diseases of cassava, Manihot esculenta Crantz (= M. utilissima Pohl), in Northeast of Brazil [...]